Prognosis Factor and KRAS Mutation Status in Association with Overall Survival in Patients with Colorectal Adenocarcinoma in Hasan Sadikin General Hospital - Ichfa Namira; Aminah, Hermin; Yulianti, Herry (Majalah Patologi Indonesia, 2025)
Introduction: Colorectal adenocarcinoma is a malignant epithelial tumor originating from the colon. Colorectal adenocarcinoma is the most common colorectal carcinoma. We aim to analyze the association between prognostic factors and KRAS mutation status with overall survival in patients with colorectal adenocarcinoma in Hasan Sadikin General Hospital. Methods: This retrospective analysis investigated the prognostic factors and KRAS mutation status in 27 patients with stage III and IV colorectal adenocarcinoma. KRAS mutations were assessed using PCR. Results: A total of 27 cases were collected and analyzed. Patients dominated with female patients (74.1%), with more than half of the patients aged>50 years old (55.6%). Most patients had tumors in their right colon (48.1%) and stage III when they were diagnosed (81.5%). 55.6% of patients had a mutation dominated by KRAS codon 12 (25.9%). The median overall survival was 13 months. Age and tumor site were statistically significant to overall survival (p<0,05); the median OS was seven months for patients whose diagnosis was < 50 years old. The median OS of patients with tumors in the right colon had a median OS of 30.6 months. Gender, KRAS mutation, and stage at diagnosis had no statistical significance on overall survival. Conclusions: Adenocarcinoma colorectal in Hasan Sadikin Hospital from 2016 until 2020 mainly occurred in women over 50 years old, with the most common location being in the right colon and most of the patients were at stage III when they were diagnosed. Most of patient’s in this study have mutation in KRAS. Age and tumor site had statistical significance on overall survival. Keywords: Adenocarcinoma colorectal, KRAS mutation, overall survival, prognostic factor